Visões da Luz - Francisco Gil (Ciências e Culturas, 2020)
This work brings together various contributions from experts in very diverse areas of knowledge, to discuss the theme 'Light' from various points of view. The subjects gathered in this work come from the areas of Physics, Philosophy, Transcendence, Chemistry, Optics, Literature, History of Sciences, History, Geography, International Relations, Biology, Psychology, Art, Cinema and Photography, Medicine and Museology. The texts partially reflect the contents presented at the interdisciplinary colloquium 'Visões da Luz' held in October 2015, on the occasion of the International Year of Light 2015, under the aegis of III-UC and open to academia and society, to teachers of the Basic and Secondary Education.